Understanding the Virality of Educational Content: A Case Study of Ruangguru's Clash of Champions in Indonesia's Digital Landscape - Kembau, Agung Stefanus; Winarko, Hilarius Bambang (Politeknik Negeri Bandung, 2025)
This study investigates the widespread diffusion of educational content by analyzing Ruangguru’s Clash of Champions campaign across Indonesian social media platforms. The proposed model suggests that content characteristics, such as relevance, surprise or uniqueness, visual quality, storytelling, and influencer endorsement, influence virality through emotional engagement, interactivity, and ease of sharing. A cross-sectional online survey of exposed users (N = 265) was analysed with PLS-SEM; adapted scales met reliability and validity standards. Findings show emotional response is a salient driver, with ease of sharing and interactivity also meaningful. Storytelling slightly outperforms influencer support in lifting perceived visual quality. Mediation tests show interactivity transmits the effect of visual quality, ease of sharing transmits information value, and emotional response transmits surprise/uniqueness. Platform differences are discussed, positioning gamification as a cross-cutting mechanism that amplifies emotion, participation, and sharing. The study extends digital virality models to an educational context and offers guidance on sequencing emotional peaks with share cues, narrative-led roles, legible interaction design, and light-touch gamification. Limitations of the study include reliance on self-reported data, a sample skewed toward younger users and focus on a single campaign.